The Effect of Hard Skill and Soft Skill on Student Entrepreneur Readiness: Evidence from Garut, Indonesia - Inten Noor Imania; Hari Mulyadi; Disman Disman; Heni Mulyani; Inten Noor Imania; Hari Mulyadi; Disman Disman (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The research is grounded in the pressing concern of rising educated unemployment and the growing expectation that entrepreneurship can serve as a strategic pathway for students to transition from job seekers to job creators, this study aims to examine the influence of hard skills and soft skills on students’ entrepreneurial readiness. Adopting a quantitative approach with a descriptive method, this study involved 156 student respondents selected through proportionate stratified random sampling. Data were collected using a closed-ended Likert-scale questionnaire. Structural Equation Modelling–Partial Least Square (SEM-PLS), supported by Smart PLS 4, was employed as the data analysis technique. The findings: (1) hard skills exert a positive and significant effect on students’ entrepreneurial readiness; (2) soft skills also have a positive and significant effect on entrepreneurial readiness; and (3) hard skills and soft skills simultaneously exert a significant influence on students’ readiness to engage in entrepreneurship. These findings are particularly valuable as they offer an affirmative and evidence-based framework for cultivating the entrepreneurs urgently needed in Indonesia. The practical implications call for a strategic transformation of entrepreneurship curricula and pedagogical approaches by educational policymakers and lecturers. Specifically, greater emphasis should be placed on the integrated, intensive, and sustained development of both hard skills and soft skills, closely aligned with the needs of the local economic ecosystem. Finally, further research employing quasi-experimental or longitudinal designs is recommended to rigorously test and refine the proposed model.